Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar IPA Siswa Kelas V SDN 27 Limau Asam - Yuris Nasri (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study was made to see the effect of contextual teaching and learning (CTL) learning models on learning outcomes of class V students. This type of research is experimental research with a design "Posttest only control design". The independent variable in this study is contextual teaching and learning ( CTL) while the dependent variable is a lecture or conventional model. The population in this study were all fifth grade students of SDN 27 limau Asam in the academic year 2020/2021 which consisted of 2 classes. In this study, using purposive sampling consisted of 25 students of class VA and 23 students of class VB. The data taken in this study were students' cognitive science learning outcomes obtained through the final test in an objective form. The results showed that the average value of the experimental class was higher than the control class where the experimental class carried out action learning using the contextual teaching and learning (CTL) learning model, while the control class did not